Exploring the Impact of Implementing Project-Based Learning Assisted by Multisim on Student Learning Outcomes in the PISAV Subject at SMK Negeri 1 West Sumatra - Fadhila Az Zahra; Ilmiyati Rahmy Jasril; Delsina Faiza; Thamrin (Sagamedia Teknologi Nusantara, 2024)
This study aims to evaluate the impact of implementing the Project-Based Learning (PjBL) model assisted by Multisim software on students' learning outcomes in the subject of planning and installation of audio-video systems (PISAV) in class XI Audio Video Engineering at SMK Negeri 1 West Sumatra. This research uses a quasi-experimental research design with a quantitative approach. The experimental design employs the One Group Pretest-Posttest Design. In this research, we conducted a pretest on one sample group before treatment (condition before), and after the treatment, we conducted a posttest (condition after). The sample in this study is the XI TAV class at SMK Negeri 1 West Sumatra. The research instruments used include pretest and posttest questions in objective form. The results of this study show that the condition after treatment has an average of 79.09, exceeding the condition before treatment, with an average of 50.18. These results suggest that the application of the PjBL learning model assisted by Multisim software has a significant impact on improving students' learning outcomes by 57.61%. Based on the hypothesis test results, it can be concluded that the t-value (21.59) is higher than the t-table (1.68), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). In conclusion, there is an improvement in students' learning outcomes in the PISAV subject after the application of the PjBL learning model assisted by Multisim software.